2018
DOI: 10.1088/1361-6463/aae113
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of titanium nanoparticles in an oxygen-starved environment. II: theory

Abstract: The nucleation and growth of pure titanium nanoparticles in a low-pressure sputter plasma has been believed to be essentially impossible. The addition of impurities, such as oxygen or water, facilitates this and allows the growth of nanoparticles. However, it seems that this route requires so high oxygen densities that metallic nanoparticles in the hexagonal Tiphase cannot be synthesized. Here we present a model which explains results for the nucleation and growth of titanium nanoparticles in the absent of re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Ar (99.9997%) is used as the process gas and is flown through the two cathodes at a total rate of 120 sccm. A small amount of O 2 is added, from outside the mesh cage, to support nanoparticle nucleation. , To efficiently add and control the O 2 content, it is diluted in Ar (95%), resulting in an effective flow of 0.025 sccm.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ar (99.9997%) is used as the process gas and is flown through the two cathodes at a total rate of 120 sccm. A small amount of O 2 is added, from outside the mesh cage, to support nanoparticle nucleation. , To efficiently add and control the O 2 content, it is diluted in Ar (95%), resulting in an effective flow of 0.025 sccm.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…A small amount of O 2 is added, from outside the mesh cage, to support nanoparticle nucleation. 30,31 To efficiently add and control the O 2 content, it is diluted in Ar (95%), resulting in an effective flow of 0.025 sccm.…”
Section: Introductionmentioning
confidence: 99%
“…been suggested that a two-body collision between a target atom and a water molecule could be enough for a dimer to form, as the target atom binds to the oxygen while a hydrogen molecule is ejected to release the excess energy. [23] Fig. 3 | Schematic image of three-body collision as two target atoms and a sputter gas atom collides.…”
Section: Nucleationmentioning
confidence: 99%
“…Above this size the cluster will, on average, only grow bigger, and it is defined as being nucleated. [23] The probability of an atom to interact with a cluster depends on the size of the cluster as well as density and motion of the atoms. A larger cluster will have a larger "target surface" and is more likely to be hit by an atom.…”
Section: Growthmentioning
confidence: 99%
“…At the same time, the thermodynamic (thermochemical) size-dependent properties of clusters, such as the enthalpy, entropy, Gibbs free energy, specific heat capacity, are of particular importance, 1,14,18,29–37 since knowledge of these attributes in a wide range of temperatures is necessary for predictive modeling chemical transformations involving clusters and nanoparticles in many areas of basic and applied research, namely, chemical vapor deposition, 4,31,38 plasma etching and other plasma-based technologies, 4,8,34,39 formation of interstellar/interplanetary dust and dusty plasma, 37,40,41 and, at last, formation of condensed phase during combustion. 42–47…”
Section: Introductionmentioning
confidence: 99%